2002
DOI: 10.1055/s-2002-32247
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiologische und psychologische Aspekte der milden Hypertonie

Abstract: The aetiopathogenesis of essential hypertension has been more intensively investigated in recent years mainly in genetic high-risk groups and patients with transitory and early forms of essential hypertension. A group of 29 patients with mild hypertension according to the WHO criteria were submitted to hypertensiological, psychological and psychophysiological specification in this study. Twenty-four hour blood measurements were performed for this purpose. The group could thus be divided into 18 patients with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Specifically, genes regulating renal function toward sodium excretion with the cytochrome enzyme class P450 ( CYP11B2, CYP4A11, CYP3A5 , see also Section Obesity: Lipid Transport and Storage) via aldosterone synthesis, and dopamine-receptor-1-mediated salt excretion, have been associated to blood pressure lowering in hypertensive rodents. Salt consumption and sodium levels related to essential hypertension have been substantiated for several decades (Svetkey et al, 1987 ; Deter et al, 1996 , 2002 , 2007a , b ; Buchholz et al, 1999 ), and been found to be influenced by emotional arousal (anger, anxiety) involving sympathetic outflow. A recent epidemiological study quantified the explained variance for trait anxiety upon high blood pressure to 6% (Lemche et al, 2016 ) in MetS.…”
Section: Traditional Hypotheses On Aetiopathologymentioning
confidence: 99%
“…Specifically, genes regulating renal function toward sodium excretion with the cytochrome enzyme class P450 ( CYP11B2, CYP4A11, CYP3A5 , see also Section Obesity: Lipid Transport and Storage) via aldosterone synthesis, and dopamine-receptor-1-mediated salt excretion, have been associated to blood pressure lowering in hypertensive rodents. Salt consumption and sodium levels related to essential hypertension have been substantiated for several decades (Svetkey et al, 1987 ; Deter et al, 1996 , 2002 , 2007a , b ; Buchholz et al, 1999 ), and been found to be influenced by emotional arousal (anger, anxiety) involving sympathetic outflow. A recent epidemiological study quantified the explained variance for trait anxiety upon high blood pressure to 6% (Lemche et al, 2016 ) in MetS.…”
Section: Traditional Hypotheses On Aetiopathologymentioning
confidence: 99%
“…Veröffentlichten in den Jahren 1992 ± 1996 immerhin sieben Autoren weniger als zwei Aufsätze, so war es diesmal nur ein Fachvertreter, der in den Jahren 1998 ± 2002 gar nicht publizierte. [18,19,27], Rüger [23], Reimer [10], Liedtke [12], Cierpka [13], Hoffmann [33,48,50], Herzog [25,42], Joraschky [34], von Rad [29, 30, 38, 72 ± 74], Senf [40,63], Fikentscher [41], Overbeck [64], Rudolf [52,53], Lamprecht [56,57], und Zepf [76]. Von den Medizinpsychologen nutzten Strauû [2,8,11,55,66 ± 68], Brähler [7,8,16,17,58,62], Neuser [20], Lang [44], Koch [59 ± 61] und Balck [75] die PPmP zur Veröffentlichung ihrer wissenschaftlichen Arbeiten.…”
Section: Ergebnisseunclassified